Knowledge gaps in our perceptual model of Great Britain's hydrology. Issue 7 (13th July 2021) - Wagener, Thorsten; Dadson, Simon J.; Hannah, David M.; Coxon, Gemma; Beven, Keith; Bloomfield, John P.; Buytaert, Wouter; Cloke, Hannah; Bates, Paul; Holden, Joseph; Parry, Louise; Lamb, Rob; et al.
Abstract: There is a no lack of significant open questions in the field of hydrology. How will hydrological connectivity between freshwater bodies be altered by future human alterations to the hydrological cycle? Where does water go when it rains? Or what is the future space–time variability of flood and drought events? However, the answers to these questions will vary with location due to the specific and often poorly understood local boundary conditions and system properties that control the functional behaviour of a catchment or any other hydrologic control volume. We suggest that an open, shared and evolving perceptual model of a region's hydrology is critical to tailor our science questions, as it would be for any other study domain from the plot to the continental scale. In this opinion piece, we begin to discuss the elements of and point out some knowledge gaps in the perceptual model of the terrestrial water cycle of Great Britain. We discuss six major knowledge gaps and propose four key ways to reduce them. While the specific knowledge gaps in our perceptual model do not necessarily transfer to other places, we believe that the development of such perceptual models should be at the core of the debate for all hydrologic communities, and we encourage others to have a similar debate for their hydrologic domain. Abstract : We suggest that an open, shared and evolving perceptual model of a region's hydrology is critical to tailor our science questions in the field of hydrology. In this opinion piece, we begin to discuss the elements of and point out some knowledge gaps in the perceptual model of the terrestrial water cycle of Great Britain.